2009
DOI: 10.1002/gps.2386
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine and care management treatment of older adults with comorbid major depressive disorder and chronic low back pain: results of an open‐label pilot study

Abstract: Objective: In older adults, major depressive disorder (MDD) and chronic low back pain (CLBP) are common and mutually exacerbating. We predicted that duloxetine pharmacotherapy and Depression and Pain Care Management (DPCM) would result in (1) significant improvement in MDD and CLBP and (2) significant improvements in health-related quality of life, anxiety, disability, self-efficacy, and sleep quality. Design and Intervention:Twelve week open-label study using duloxetine up to 120 mg/day + DPCM.Setting: Outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 70 publications
(65 reference statements)
0
23
1
3
Order By: Relevance
“…Among older adults, there is a bi-directional relationship between low back pain and depressive symptoms as each is a risk factor for the other. (41–43) Karp et al asserted that the relationship between chronic low back pain and depression “can lead to a cycle of demoralization, physical and psychosocial disability, and exacerbated medical and psychiatric comorbidity.”(44) In the presence of both back pain and depressive symptoms, it may be vitally important to address both issues simultaneously to have good outcomes for either problem.…”
Section: Discussionmentioning
confidence: 99%
“…Among older adults, there is a bi-directional relationship between low back pain and depressive symptoms as each is a risk factor for the other. (41–43) Karp et al asserted that the relationship between chronic low back pain and depression “can lead to a cycle of demoralization, physical and psychosocial disability, and exacerbated medical and psychiatric comorbidity.”(44) In the presence of both back pain and depressive symptoms, it may be vitally important to address both issues simultaneously to have good outcomes for either problem.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroimaging study was embedded in several open-label treatment intervention trials for LLD conducted at the University of Pittsburgh Advanced Center for Intervention and Services Research for Late-Life Mood Disorders (ACISR) from 2004 and 2011 (Karp et al, 2010; Reynolds et al, 2011; Reynolds et al, 2010). Additional description of these trials is provided in the online supplemental data.…”
Section: Methodsmentioning
confidence: 99%
“…59 In older patients with comorbid major depression and CLBP, duloxetine was effective in improving both conditions, with improvements in pain preceding improvements in depression. 60 Past analyses of randomized controlled trials of duloxetine have shown that its effects on pain using a McGill Pain Questionnaire are independent of its antidepressive effects. 58 Recent preclinical series provide some insight into the MOA of duloxetine against neuropathic pain, including its ability to confer antinociceptive effects in mechanical hyperalgesia 61 and interact with serotonin 2A receptors in DPN.…”
Section: Efficacy Of Opioid Agonists For Chronic Painmentioning
confidence: 99%